Sexual Expression in Institutional Care Settings for Older People: An Interactive Multi-Media CDRom. - Montague, Jane (Ageing & Society, 2004)
A review of Sexual Expression in Institutional Care Settings for Older People: An Interactive Multi-Media CD-ROM, by Gill Hubbard, Ailsa Cook, Susan Tester, and Murna Downs, is presented. Good overall clarity and accessibility make this CD-ROM a good introduction for various audiences to research on sexual expression among older institutional care patients.